Library and information infrastructure of the regions of the Azerbaijan Republic: its development, current state and ways of modernization. (Experience of the Sheki-Zakatala Economic Region) - Heydar, Mahammadli Dashgin (Technium Social Sciences Journal, 2023)
The 21st century is characterized as an age of exchange of science, culture, social information among the countries of the world and as a century of information. This century has also entered the history of mankind as a century of high cultural progress. In the 21st century, the issue of informatization, operative reception and transmission of information has become an important factor, and from a legal point of view, has been regulated by the Law of the Republic of Azerbaijan “On information, informatization and protection of information” adopted on April 3, 1998 by the signature of the national leader Heydar Aliyev. Global changes, which take place in the society, accelerate the development of modern library science, bibliography, bibliology and information. One of the priority areas in front of these sciences is the study of the library and information infrastructure of the country and its various regions. The territorial principle has been taken as one of the main principles in organizing the library system in our republic according to the fifth article of the Law of the Republic of Azerbaijan “on Library Work” − “The fundamentals of the organization of library system” endorsed on December 29, 1998, by the signature of national leader Heydar Aliyev. In accordance with the “State Program” of socio-economic development of the regions in the Republic of Azerbaijan (2004-2008), our republic is divided into 10 economic regions. One of them is the Sheki-Zagatala economic region. The economic region includes Sheki, Gakh, Zagatala, Gabala, Oghuz and Balakan economic districts. The economic region, with an area of ​​8.96 thousand square kilometers, accounts for 10.3% of the country’s territory. According to the statistical data of 2017, the economic region with a population of 616,800 people accounts for 6.5% of the country’s population. Thus, the economic region is endowed with rich nature, diverse natural and information resources. Therefore, writing a thesis on the topic − “Library and information infrastructure of the Sheki-Zagatala economic region of the Republic of Azerbaijan: Its development, current status and ways of modernization” is of great relevance.